Effectiveness of Occupational Health Promotion Programs on Cardiometabolic risk factors: A Systematic Review and Three-Level Meta-Analysis - Godono, Alessandro; Leso, Veruscka; Paradisi, Ettore; Carena, Elisa; Picciaiola, Maria Vittoria; Schneider-Kamp, Anna; Ciocan, Catalina; Bert, Fabrizio; Veglio, Franco; Boffetta, Paolo; Iavicoli, Ivo (La Medicina del Lavoro, 2025)
Background: This study aimed to evaluate the effectiveness of workplace-based health promotion programs targeting cardiometabolic risk factors. Methods: We conducted a systematic review and three-level random-effects meta-analysis following PRISMA guidelines, covering studies published from January 2019 to September 2024. Eligible studies included randomized controlled trials (RCTs) and quasi-experimental (QE) designs assessing workplace interventions to reduce cardiometabolic risks in adult workers. Twelve outcomes were considered. Subgroup analyses and meta-regressions were performed to explore sources of heterogeneity. Certainty of evidence was evaluated using GRADE assessment tool. Results: Forty-four studies (30 RCTs, 14 QE) involving 49,813 participants were included. Significant improvements were found in nine of twelve outcomes. These included reductions in BMI (–0.61kg/m²; [–0.93; –0.29]), body weight (–2.43kg; [–3.48; –1.38]), waist circumference (–3.46cm; [–5.21; –1.71]), body fat (–1.58%; [–2.40; –0.76]), systolic (–3.75mmHg: [–5.67; –1.82]) and diastolic (mmHg; [-3.58; -1.29]) blood pressure, LDL cholesterol (–5.9 mg/dL; [–11.6; –0.12]), and an increase in HDL cholesterol (2.76 mg/dL; [0.42; 5.09]). All significant outcomes were supported by moderate-to-high certainty evidence except LDL cholesterol, which was rated very low. Non-significant results were observed for total cholesterol, triglycerides and FBG. High heterogeneity was observed. Pre-existing health conditions, author and duration of intervention partially explained between-study heterogeneity. Conclusions: Workplace health promotion programs were associated with improvements in various cardiometabolic health indicators. Greater effectiveness was observed in interventions targeting high-risk populations, delivered by physicians or qualified health professionals, and implemented over shorter durations. Findings support the integration of such programs into occupational health policies and broader public health strategies. Future research should optimize intervention designs, extend follow-up, and consider integrated approaches to maximize long-term benefits.